chem & bio 3D, finder and bioviz : chem & bio office desktop 2010 for Windows : user's guide (Cambridge, MA, 2010)
This ultimate chemistry & biology suite is designed to meet the needs of both chemists and biologists. ChemBioOffice 2010 includes Chem&Bio Draw : chem & bio drawing standard, Chem&Bio3D finder and Bioviz, enterprise solutions and databases including E-notebook and ChemBioOffice : Chemistry, biology and knowledge
Keywords: Biochemistry,Biochemistry